2020
DOI: 10.1186/s13765-020-00526-w
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal remediation in soil with chemical amendments and its impact on activity of antioxidant enzymes in Lettuce (Lactuca sativa) and soil enzymes

Abstract: Chemical amendments have been used to remediate soils contaminated with heavy metals. However, there is little understanding on the impacts of these amendments on the physiological and biochemical functions of plants and soil. This study used in situ microcosm experiment to understand the effect of chemical amendments on antioxidant and soil enzyme activity in plant and soil with respect to heavy metal reduction. Three chemical amendments-acid mine drainage sludge (AMDS), limestone (LS), and steel slag (SS)-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The pH and electrical conductivity of the samples were determined for a 1:5 soil:water ( w / v ) suspension using a pH meter and conductivity meter (MP220, Mettler Toledo, Columbus, OH, USA) [ 4 ]. The cation exchange capacity was analyzed using the 1 M CH 3 COOH extraction method [ 2 ]. The soil organic content was measured as described by Walkley and Black.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pH and electrical conductivity of the samples were determined for a 1:5 soil:water ( w / v ) suspension using a pH meter and conductivity meter (MP220, Mettler Toledo, Columbus, OH, USA) [ 4 ]. The cation exchange capacity was analyzed using the 1 M CH 3 COOH extraction method [ 2 ]. The soil organic content was measured as described by Walkley and Black.…”
Section: Methodsmentioning
confidence: 99%
“…The soil organic content was measured as described by Walkley and Black. Effective phosphoric acid was determined using the Bray No.1 method with molybdenum blue dye and measured on a UV spectrophotometer (UV-1800, Shimadzu, Kyoto, Japan) [ 2 ]. The inorganic nitrogen content, as NH 4 -N and NO 3 -N, was determined using a QuikChem automated ion analyzer (QuikChem 6000 Series, Lachat Instruments, Milwaukee, WI, USA), after extraction with 2 M KCl [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metals, especially Cd, can interfere with plant physiological processes by stimulating H 2 O 2 generation and inhibit plant growth ( Lai et al., 2020 ). Previous studies have shown that soil Cd pollution in farmlands is closely related to the excessive application of chemical fertilizers and pesticides and wastewater irrigation ( Hong et al., 2020 ). Cd in soil is easily absorbed by plant roots and transmitted upward to other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the remediation methods of heavy-metal-contaminated soil are mainly divided into physicochemical remediation [10,11], chemical remediation [12], phytoreme-Sustainability 2021, 13, 14041 2 of 18 diation [13], and bioremediation [14]. Physicochemical remediation involves changing the pH, redox conditions, or ion composition of soil by adding amendments to achieve the purpose of passivating heavy metals in the soil [15].…”
Section: Introductionmentioning
confidence: 99%